Spectrum of RB1 Germline Mutations and Clinical Features in Unrelated Chinese Patients With Retinoblastoma - Lan, Xiaoping; Xu, Wuhen; Tang, Xiaojun; Ye, Haiyun; Song, Xiaozhen; Lin, Longlong; Ren, Xiang; Yu, Guangjun; Zhang, Hong; Wu, Shengnan (Frontiers in Genetics, 2020)
Retinoblastoma (Rb) is a primary intraocular malignant tumor that occurs primarily in children, and results from loss-of-function mutations in the RB transcriptional corepressor 1 (RB1) gene. Genetic testing forms the basis of genetic counseling for affected families, as well as for clinical management of this disease. The aim of this study was to identify germline RB1 mutations and correlate the identified mutations with the clinical features of Rb patients. Genomic DNA was isolated from peripheral blood of 180 unrelated Rb patients and their parents (118 unilaterally and 62 bilaterally affected probands). Mutations in the RB1 gene, including the promoter region and exons 1–27 with ﬂanking intronic sequences, were identified by Sanger sequencing. The samples with negative sequencing results were further subjected to methylation-specific multiplex ligation-dependent probe amplification (MS-MLPA) to detect gross deletions or duplications. Sixty-three distinct mutations were identified in 75 of the 180 (41.7%) probands. Of the 75 patients carrying RB1 mutations, 56 developed bilateral Rb, while 19 developed unilateral Rb. The total detection rates for bilateral and unilateral Rb were 90.3% (56/62) and 16.1% (19/118), respectively. Among the 75 patients, the spectrum of mutation types comprised 29.3% (22/75) nonsense mutations, 22.7% (17/75) splicing mutations, 17.3% (13/75) small insertions/deletions, 16.0% (12/75) large deletions/duplications, and 13.3% (10/75) missense mutations, while only 1% (1/75) of the mutations were in the promoter region of the RB1 gene. Age at diagnosis was significantly different (p < 0.01) between patients with positive and negative test results for germline RB1 mutations. A c.2359C>T mutation (p.R787X) was identified in identical twins, but one child was affected bilaterally and the other unilaterally. Of the 5 patients with deletion of the entire RB1 gene, the deletion of 2 patients was inherited from unaffected parents. In conclusion, in this study, we provide a comprehensive spectrum of RB1 germline mutations in Chinese Rb patients, and describe the correlations among RB1 mutations, age at diagnosis, and laterality; moreover, we report that the clinical features of individuals carrying an identical mutation in the RB1 gene were highly variable, indicating that the pathogenesis of Rb is more complicated than currently believed.